Daily Food Insecurity and Heart Rate Variability Among Healthy Low-Income Adults: A Longitudinal Pilot Study Over Two Seasonal Months - Dou, Nan (Curr Dev Nutr, 2021)
OBJECTIVES: Food insecurity (FI) is prevalent among low-income adults and is related to increased stress. Heart rate variability (HRV) is associated with adverse health and a known indicator for stress vulnerability. However, the relationship between FI and HRV is unclear. Our study aims to study the associations between FI and ultra-short-term HRV (5 minutes) at daily basis. METHODS: A total of 22 healthy low-income adults were recruited in fall 2019 and 18 were followed up in winter 2020. Data on FI and HRV were collected over a 3-week-long wave in each surveyed month (2nd – 4th week). Daily FI was assessed using the adapted USDA adult module on the provided smartphones. Each day, a 5-minute heart rate was recorded using the Polar H7 sensor, yielding a number of HRV metrics in two domains. SDNN, Rmssd, and pNN50 are time-domain metrics quantifying the amount of variability in interbeat interval (the higher the ‘better’). LF/HF Ratio is a frequency-domain metrics estimating the distribution of power into frequency bands (the lower the ‘better’). The Time Varying Effect Models were used to estimate the association between daily FI and ultra-short-term HRV metrics as a function of study day. RESULTS: A total of 606 person-days (response rate = 72.1%) of data in FI and HRV was collected. In fall, higher FI score was significantly associated with lower lnRmssd at day 19 (b = −0.13) and 20 (b = −0.12), lower Pnn50 at day 20 (b = −0.13), and higher LF/HF ratio from day 1 to 5 (b ranges 0.29–0.88). In winter, higher FI score was related to lower lnRmssd at day 18 (b = −0.24) and 19 (b = −0.27), lower Pnn50 from day 17 to 19 (b ranges −10.99 to −7.79), and higher LF/HF ratio from day 9 to 11 (b ranges 0.78–1.22) and day 18 to 20 (b ranges 1.17–2.40). CONCLUSIONS: Across the 2 months spanning two seasons, our pilot study found that daily FI was significantly and consistently associated with suboptimal time-domain HRV metrics in the last few days of the study months. Results for the frequency-domain also support a time-varying impact of FI on HRV. The preliminary results support a potential more profound impact of FI on stress vulnerability, particularly by the end of the months. FUNDING SOURCES: The National Center for Advancing Translational Sciences, National Institutes of Health (UL1TR002014) and the Broadhurst Career Development Professorship for the Study of Health Promotion and Disease Prevention.